1986
DOI: 10.1021/j100280a033
|View full text |Cite
|
Sign up to set email alerts
|

Metal-sensitive bands in the Raman and infrared spectra of intact and metal-substituted chlorophyll a

Abstract: Raman and infrared spectra of intact and metal-substituted chlorophyll a were observed in the solid state and in solution. Ni, Cu, Zn, and Ag were used to substitute Mg. Nine series of metal-sensitive bands were found in both the Raman and infrared spectra in the solid state. The frequencies of these metal-sensitive bands are considered to be linear functions of the Ct-N distance (Ct is the center of the chlorin ring and N is the nitrogen atom in the pyrrole ring), by analogy with the relationships established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
50
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 0 publications
3
50
0
Order By: Relevance
“…Rate constants for the reactions were determined from the slope of the plot of equation (3) against time over fixed temperatures of 313, 322.8 and 332.9 K. Rate constants at these temperatures are presented in Table 1. The kinetic stability of the cobalt ion in the centre of the chlorophyll macrocycle is comparable to results obtained by other workers [19][20][21] in this field, which show that transition metals coordinated to the chlorophyll macrocycle provide an increase in the stability 22 of the chlorophyll macrocycle. This stability is reflected in the activation energy of the electron transfer reaction obtained.…”
Section: Resultssupporting
confidence: 87%
“…Rate constants for the reactions were determined from the slope of the plot of equation (3) against time over fixed temperatures of 313, 322.8 and 332.9 K. Rate constants at these temperatures are presented in Table 1. The kinetic stability of the cobalt ion in the centre of the chlorophyll macrocycle is comparable to results obtained by other workers [19][20][21] in this field, which show that transition metals coordinated to the chlorophyll macrocycle provide an increase in the stability 22 of the chlorophyll macrocycle. This stability is reflected in the activation energy of the electron transfer reaction obtained.…”
Section: Resultssupporting
confidence: 87%
“…These modes often arise from vibrations delocalized on the Chl a macrocycle, some in the low frequency range (around 300 cm Ϫ1 ), which involve the central magnesium atom, and others in the mid-frequency range (800 -1500 cm Ϫ1 ) sensitive to the Chl a macrocycle conformation (26). However, none of these modes in the low to mid frequencies undergo shifts large enough so that they can be used for conclusive analysis of pigment protein complexes containing as many chlorophylls as LHCs.…”
Section: Resultsmentioning
confidence: 99%
“…, are sensitive to the macrocycle core size and have been widely used to assess the number of axial ligands bound to the central magnesium of these molecules (26,28). This methine bridge mode is observed at about 1600 cm Ϫ1 when the central magnesium is six-coordinated, and is up-shifted to 1610 -1615 cm Ϫ1 for five-coordinated magnesium.…”
mentioning
confidence: 99%
“…For excitation conditions within the Soret electronic transition, it has been shown that resonance Raman spectra of chlorophyll a contain a number of bands that may be used for determining accurately the conformation of these molecules in vitro, as well as in their protein binding pocket (21,22). As the molecular conformation of chl depends in particular on the number of axial ligands on the central magnesium atom, the coordination number of this atom may be deduced from the frequency of some of these bands (8).…”
Section: Resultsmentioning
confidence: 99%